Glycyrrhiza uralensis Fisch. suppresses cell migration via ROS and JAK/STAT signalling pathways in Drosophila - Zhou, Fangfei; Lu, Qingge; Kong, Lingyu; Wang, Sitong; Zhang, Haixia; Zhao, Meng; Hu, Yue; Wu, Fanwu; Wu, Chenxi (Frontiers in Pharmacology, 2025)
BackgroundCancer is a global public health crisis and the leading cause of death among middle-aged and older individuals, with its incidence increasingly shifting toward younger populations. Approximately 90% of the patients succumb to advanced metastasis, and effective treatments remain elusive. The specific molecular mechanisms underlying cancer cell invasion and migration remain poorly understood, hindering the development of effective targeted therapies. Therefore, inhibiting or reversing cancer cell invasion and migration may be crucial for reducing mortality. Our previous research revealed that the five drugs (FD), derived from Xuefu Zhuyu Decoction (XFZYD), play a significant role in inhibiting cell migration.Hypothesis/purposeThis study aims to explore the main drug components of FD and investigate the underlying mechanism in inhibiting cell migration.MethodsWe used the Drosophila ptc>scrib-IR cell migration model to investigate the effects of FD. FD was disassembled and analyzed using an orthogonal design. Drug extracts were prepared and administered to Drosophila larvae. We assessed the effects of FD on cell migration, reactive oxygen species (ROS) levels, and gene expression.ResultsIn FD disassembled recipes and orthogonal test design, a significant difference was observed in the intervention with or without Glycyrrhiza uralensis Fisch. (GUF) in migrating cell number (P < 0.01), which emerged as a more potent inhibitor of FD from XFZYD in cell migration. High-performance liquid chromatography revealed that GUF and its extract contained effective medicinal components, namely glycyrrhizic acid, liquiritin, liquiritigenin, and glycyrrhetinic acid. Moreover, GUF at 4.0 mg/mL displayed strong inhibitory effect in migrating cell number and distance when compared with model, XFZYD or FD. Excessive ROS can activate the JAK/STAT signaling pathway and promote the EMT process. GUF inhibited ptc>scrib-IR-induced cell migration by reducing ROS levels, JAK/STAT signalling, and the transcription of upd2, upd3, hop and socs36E. Finally, GUF rescued the altered expressions of the epithelial-mesenchymal transition (EMT)-related proteins, including matrix metalloproteinase 1 (MMP1), β-integrin and E-cadherin, triggered by cell migration.ConclusionOur findings demonstrate that GUF may serve as a promising candidate for targeting advanced metastatic tumors by suppressing ROS-mediated JAK/STAT signaling and EMT.